Overgrowth of reef organisms by benthic cyanobacteria in the Colombian Caribbean
<span data-sheets-value=""1":2,"2":"Blooms of marine benthic cyanobacteria seem to be recurrent at various reef sites of the Colombian Caribbean. However, their effect on local reef communities has not been assessed. In this note we document some interac-tions between cyanobacteria and reef organisms."" data-sheets-userformat=""2":15353,"3":"1":0,"6":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"7":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"8":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"10":1,"11":4,"12":0,"14":"1":2,"2":0,"15":"Times New Roman","16":11">Blooms of marine benthic cyanobacteria seem to be recurrent at various reef sites of the Colombian Caribbean. However, their effect on local reef communities has not been assessed. In this note we document some interactions between cyanobacteria and reef organisms. , number=2, journal=Revista Mutis, author=Puyana, Monica and Prato, Julián, year=2013, month=dic., pages=58–60